Long-Run Relationship between Marketing of Bank Services and the Performance of Deposit Money Banks in Nigeria - O., EmenikeKalu; Obasi, Ray (International Journal of Economics, Business and Management Studies, 2016)
This paper investigates whether long-run relationship exists between marketing of bank services and deposit money banks (DMBs) in Nigeria using Monthly data obtained from the Central Bank of Nigeria statistical database from January 2002 to December 2014. Univariate statistics shows that both marketing of bank services and bank performance variables have positive returns, positive skewness and leptokurtic. In addition, they are not normally distributed. The ADF unit root tests show that the marketing of bank services and DMBs performance indicator series are integrated of order one (i.e., I(1)). The empirical results obtained from the cointegration model indicate evidence of positive long-run relationship between marketing of bank services on bank profitability in Nigeria. We recommend among others that deposit money banks should insist on engaging marketing professionals to undertake the marketing services in their banks.